2011
DOI: 10.1590/s0034-89102011000300015
|View full text |Cite
|
Sign up to set email alerts
|

Femicídios: homicídios femininos no Brasil

Abstract: OBJECTIVE:To assess female homicide rates due to aggression according to sociodemographic and health indicators. METHODS: RESULTS:The standardized female homicide rate due to aggression was 4.1/100,000 during the study period. After adjustment, three variables remained signifi cantly associated with female homicides: birth rate (p = 0.072), percentage of Evangelicals (p = 0.019) and male homicides due to aggression (p < 0.001). The model had a predictive power of 69% (r2 = 0.699). The Brazilian states of Espí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1
50

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(106 citation statements)
references
References 21 publications
4
51
1
50
Order By: Relevance
“…It is thought that this high rate is associated to the belief that crimes against women are justified because they are private matters. In these cases, impunity is the result of historical evolution and the fact that there is no political will to adequately address violence against women in a more incisive way 7,[15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is thought that this high rate is associated to the belief that crimes against women are justified because they are private matters. In these cases, impunity is the result of historical evolution and the fact that there is no political will to adequately address violence against women in a more incisive way 7,[15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Particularly important are the Maria da Penha law that established mechanisms to curb violence against women 15 and Law 13.104 that classifies femicide as a heinous crime, providing for harsh penalties 18 . However, although a legal framework is in place to suppress this type of violence, there are shortfalls in the application of legislation, ranging from invisibility that leads to the under-reporting of violence against women 16 to the difficulties in establishing a substantive network of care for addressing this issue effectively 19,20 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Campero et al 5 (2006), analyzing deaths of women who had suffered violence, observed a mean age of 19.7 in women who died from external causes during pregnancy. Granja et al 12 (2002) emphasized that death by suicide among pregnant women occurred in women aged younger than 25.…”
Section: Discussionmentioning
confidence: 99%